Possibilities for nursing interventions in the prevention of falls in the elderly: a review - Santos, Bebiano Will dos (2021)
Objective: To identify the nursing interventions that increase the home safety of elderly and prevent falls. Method: Integrative literature review guided by the question: “What nursing interventions are adequate to prevent falls in the elderly at home?”. From May to June 2018, there was a search for studies in EBSCO, B-On, SCOPUS, ISI, and JBI. Results: The 13 studies recommend interventions that were organized in five categories: environmental risk assessment; advices on changes; adaptation of the space and equipment; assistance in the purchasing of support products and cognitive-behavioral strategies that increase the safety of the elder in the use of the physical space at home. Conclusion: The possible interventions for the prevention of falls include: environmental risk assessment; advices on changes; adaptation of the space and equipment; assistance in the purchasing of support products; and cognitive-behavioral strategies that increase the safety of the elder in the use of the physical space at home.